Cross sectional study on food safety knowledge, attitudes, and practices of food handlers in Lahore district, Pakistan. Issue 11 (November 2021) - Ahmed, Muhammad Hashaam; Akbar, Ali; Sadiq, Muhammad Bilal
Abstract: Annually, millions of the people suffer from foodborne diseases which are mainly associated with poor food handling practices. The poor food safety knowledge and practices increase the risk of food contamination and foodborne diseases. The aim of this study was to evaluate the relationship between demographic attributes and food safety knowledge, attitudes, and practices (KAP) of food handlers (chefs and servers) working in small-scale restaurants, hotels and eateries in Lahore, Pakistan. A structured questionnaire including questions related to demographic characteristics and food safety KAP attributes of food handlers (n = 202) was used to collect the responses. The responses of food handlers were statistically analyzed using Spearman Correlation and Chi-Square tests. The results showed that a large proportion of food handlers had good attitudes towards food safety and followed good food safety practices (FSP) but had poor food safety knowledge (FSK). Demographic characteristics of food handlers i.e. level of education, professional category, current job tenure, and total food service industry experience were significantly (p < 0.05) associated with FSK, FSA, and FSP. FSK was found to be moderate to strongly correlated with FSP of food handlers (rs = 0.675), whereas FSA was found to be strongly correlated with FSP (rs = 0.733). The study highlighted the importance and impact of food safety knowledge on food safety practices and overall perspective of food handlers working in restaurants. Graphical abstract: Image 1 Abstract : Food safety knowledge, Food safety attitudes, Food safety practices, Food handlers, Food safety legislation.